Kontribusi Ornamen Pura Dalem Segara Madhu Terhadap Mata Kuliah Estetika Hindu Pada Prodi Filsafat Hindu STAHN Mpu Kuturan Singaraja - Ayu Veronika Somawati; I Made Gami Sandi Untara (Jayapangus Press, 2023)
Hindu philosophy is one of the study programs of STAH Negeri Mpu Kuturan Singaraja which contributes to studying various philosophical thoughts both in general and about Hindu philosophy, as well as studying various religious phenomena. This is important to do so that people, especially Hindus, understand the philosophical or tattva values ​​of all religious activities carried out. To examine these matters, especially for students, of course, learning media are needed that can make it easier for students to understand certain concepts, especially those that are abstract. One of the courses that require concrete learning media is the Hindu Aesthetics subject. The choice of learning media that can be used in this course is the ornamens found in Dalem Segara Madhu Temple, Jagaraga Village, Sawan District, Buleleng Regency. This is due to the uniqueness of the carvings found on the paduraksa in this temple. By using a qualitative descriptive method, this paper examines the contribution of the ornamens in Dalem Segara Madhu Temple to the Hindu aesthetics subject at the Hindu Philosophy study program. The results of the study are that the ornamens found in Dalem Segara Madhu Temple can be included in learning about the concept of creating art in society. Thus, students can understand the theory of Hindu aesthetics and explain the relationship between aesthetic values ​​and philosophical values ​​contained in these ornamens.